Branding Strategies to Enhance the Appeal of Cultural Heritage Sites for International Tourists - Iswanto, Dedy; Irsyad, Ziqrurrahman; Sudarta; Fuzail, Muhammad; Gamri, Muhammad (PT. Sangadji Media Publishing, 2025)
Purpose – This study explores the application of branding in enhancing the attractiveness of cultural heritage sites for international tourists. It investigates the role of branding in shaping tourist perceptions, increasing revisit intention, and improving visitor satisfaction. Design/method/approach – A Systematic Literature Review (SLR) was conducted using literature from Scopus, DOAJ, and Google Scholar. Keywords like